Brussels at the heart of urban legends? - Aurore Van de Winkel (Brussels Studies, 2011)
This article presents urban legends told in Brussels which reflect an urban imagination crossed with local characteristics. Presented as news items although their truthfulness is questionable, these stories mentioning Brussels tell of attacks or harm committed against an anonymous person or the friend of a friend, in everyday public spaces, places of constant coming and going, personal itineraries or familiar shops. These legends feature the confrontation with others, machines or nature, and present Brussels as a dangerous place where security is everybody’s business. These legends serve as warnings and allow people to reassert their identity by designating scapegoats. The stories which take place in Brussels may, however, come from elsewhere and be told around the world. The places mentioned are lures intended to increase a feeling of proximity, affects and an identification with the characters. Brussels is featured as an empty shell with the same characteristics as every big city in industrialised western countries – an empty shell necessary for the contemporary imagination.